PERANCANGAN DATABASE SISTEM INFORMASI MANAJEMEN PENJUALAN TOKO AFRIDA CAKE MENGGUNAKAN ERD - Dea Saptri, Tania Daniat, (TEKNOFILE : Jurnal Sistem Informasi, 2025)
ABSTRACT Afrida Cake Shop is a Micro, Small and Medium Enterprise (MSME) which operates in the field of selling various types of cakes and snacks in Tembilahan. The current sales process is still carried out manually, which can causenefficiencies in managing sales data and stock. To overcome this problem, a web-based Sales Management Information System was designed which aims to increase operational efficiency and accuracy of sales data and inventory. This system was designed using the Waterfall method, which includes the stages of requirements analysis, system design, implementation, testing and maintenance. Tools used in design include data flow diagrams, Entity Relationship Diagrams and user interface design. By implementing this system, it is hoped that the Afrida Cake Shop can manage sales data and inventory more effectively and efficiently, as well as improve the quality of service to customers.